First Surveillance of Violence against Women during COVID-19 Lockdown: Experience from “Niguarda” Hospital in Milan, Italy - Nittari, Giulio (Int J Environ Res Public Health, 2021)
Violence against women emerges with tragic regularity in the daily news. It is now an evident trace of a dramatic social problem, the characteristics of which are not attributable to certain economic, cultural, or religious conditions of the people involved but affect indiscriminately, in a unanimous way, our society. The study is a survey about the number of hospital admissions due to episodes attributable to violence against women, recorded by the Niguarda Hospital in Milan in the period 1 March–30 May from 2017 to 2020. This period, in 2020, corresponds to the coronavirus Lockdown in Italy. All the medical records of the Emergency department were reviewed, and the extracted data classified in order to identify the episodes of violence against women and the features of the reported injuries and the characteristics of the victims. The data did not show an increase in the number of cases in 2020 compared to previous years, but we did find a notable increase in the severity of injuries.